2020
DOI: 10.1111/aas.13685
|View full text |Cite
|
Sign up to set email alerts
|

Post‐operative opioid‐related adverse events with intravenous oxycodone compared to morphine: A randomized controlled trial

Abstract: Background The value of intravenous oxycodone compared to morphine remains controversial. The purpose of this trial was to compare opioid‐related adverse events (ORAES) of intravenous oxycodone and morphine after total hip arthroplasty. Methods Patients scheduled for total hip arthroplasty were enrolled in this study of post‐operative pain treatment with intravenous oxycodone or intravenous morphine (ratio 1:1). After surgery, patients received similar drug regimens for titration in the post‐operative care uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
2
4
1
Order By: Relevance
“…Previous studies have shown that the adverse effects of oxycodone included nausea, vomiting, and dizziness (19)(20)(21). There was no significant difference in the incidence of postoperative nausea and vomiting among three groups in our study.…”
Section: Discussioncontrasting
confidence: 55%
“…Previous studies have shown that the adverse effects of oxycodone included nausea, vomiting, and dizziness (19)(20)(21). There was no significant difference in the incidence of postoperative nausea and vomiting among three groups in our study.…”
Section: Discussioncontrasting
confidence: 55%
“…There are some data which suggest that oxycodone is better than morphine after surgery but this is controversial and may be related to variable equipotency ratios in the different studies. In a recent randomized study; however, Cuvillon et al4 showed that oxycodone did not reduce the rate of opioid-related adverse events. In the present study, drugs administered and doses were collected and a reduced use of oxycodone was found but pain-related sores are not provided.…”
Section: Commentarymentioning
confidence: 95%
“…In the PACU, patients experiencing pain with an NRS >3 (NRS 0–10; from 0=no pain to 10=the worst pain imaginable) were given an intravenous titration of 3 mg of the drug under study (2 mg if body weight <60 kg) at 5 min intervals until an NRS ≤3 was obtained according to the protocol 20…”
Section: Methodsmentioning
confidence: 99%